THE ROLE OF DISPORA IN ENHANCING SPORTS ACHIEVEMENTS IN EAST KALIMANTAN - Wartini, Sri; Haryaka, Usfandi (STIT Ibnu Rusyd Tanah Grogot, 2024)
This study aims to identify and analyze the Youth and Sports Office's (DISPORA) role in enhancing sports achievements in East Kalimantan. Sports play an important role not only in maintaining physical fitness but also as a means to elevate the dignity of individuals, groups, and nations. Sports achievements, often measured by medals, result from a development process that begins at an early age. Therefore, collaboration between the government, educational institutions, and sports organizations is essential to creating synergy in the management and development of sports. This research uses a descriptive approach with observation, interviews, and documentation studies to collect data on the existing sports development system in East Kalimantan. The findings show that DISPORA plays a role in various aspects of sports development, from promoting sports to discovering talented athletes to providing adequate facilities and infrastructure. The development involves educational, achievement, and recreational sports, which complement each other in creating a healthy sports ecosystem. However, challenges such as the limited number and quality of sports educators, inadequate facilities, and funding constraints pose barriers to developing an effective sports development system. Therefore, improvements in the recruitment and training of educators, the development of sports facilities, and more efficient allocation of funding are needed to ensure the sustainability of sports development programs. With the proper steps, sports achievements in East Kalimantan can improve, producing athletes who compete at national and international levels and building a healthier and more accomplished society.